2013
DOI: 10.1111/jpc.12280
|View full text |Cite
|
Sign up to set email alerts
|

Acute costs and predictors of higher treatment costs for major paediatric trauma in New South Wales, Australia

Abstract: The high financial cost of paediatric patient treatment highlights the need to ensure prevention remains a priority in Australia. Hospitals tasked with providing trauma care should be appropriately funded and future funding models should consider trauma severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Falls and road trauma accounted for 33% and 22% of acute care costs, respectively. Further, they reported children 1–5 years had the highest total costs; however, infants had the highest average cost for major paediatric trauma 19 . We report the cost of acute admissions for 4361 children was $13 million, with 46% from transportation‐related injuries, followed by 39% from falls.…”
Section: Discussionmentioning
confidence: 83%
“…Falls and road trauma accounted for 33% and 22% of acute care costs, respectively. Further, they reported children 1–5 years had the highest total costs; however, infants had the highest average cost for major paediatric trauma 19 . We report the cost of acute admissions for 4361 children was $13 million, with 46% from transportation‐related injuries, followed by 39% from falls.…”
Section: Discussionmentioning
confidence: 83%
“…This is particularly true in this study as SCN and NICU admissions were reported together, with admission to NICU distinguished in the cost analysis by use of mechanical ventilation. There is also evidence that average cost funding by peer group, such as HRGs or AR‐DRGs, underestimates the actual costs incurred by the hospital for paediatric intensive care . Micro‐costing of intensive care costs applies more patient‐specific costs; however, this method requires a great detail of data collection .…”
Section: Discussionmentioning
confidence: 99%
“…Drowning disproportionately impacts young children where the greatest health losses are attributed. Drowning attracts the highest economic burden with respect to paediatric trauma treatment costs 52 and high mortality risk within 30 days of hospitalisation for paediatric patients when compared to other injury mechanisms 53 . Across the general population, drowning is also a preventable cause of public health‐related harm.…”
Section: Implications For Public Healthmentioning
confidence: 99%